Advancing cybersecurity through proactive cyber threat intelligence - Zainuddin, Ahmad Anwar; Abd Rahim, Noor Hayani; Ahmad Nordin, Nabilah; Amerolazuam, Amysha Qistina; Nik Mohd Kamal, Nik Nor Muhammad Saifudin; Sapuan, Muhamad Syariff (Center for Islamization, International Islamic University Malaysia, 2024)
In the context of hikmah, the application of artificial intelligence (AI) can significantly enhance our defence against the increasingly severe and frequent cyberattacks of today. The dynamic, elusive, resilient, and complex nature of new-generation threats makes it challenging for traditional security systems based on heuristics and signatures to keep up. By incorporating AI, organisations can adopt a proactive approach, collecting and disseminating real-time cyber threat information with greater precision and efficiency. Cyber Threat Intelligence (CTI) mining, a rapidly growing field, leverages AI to find, process, and evaluate crucial data regarding cyber risks. However, many businesses still primarily focus on fundamental use cases, such as integrating intrusion prevention systems, security information and event management, and threat data feeds with existing network and firewall systems. This article surveys and investigates various data sources related to CTI mining and explores the potential paths for future research in this area, emphasising the role of AI guided by hikmah principles in enhancing cybersecurity. The findings indicate that AI-guided CTI mining, when aligned with hikmah principles, can create a more ethically robust cybersecurity framework. Future work should investigate the long-term impacts of such an integration on threat detection and mitigation across various sectors.